Transcription Factors in Heart: Promising Therapeutic Targets in Cardiac Hypertrophy - Kohli, Shrey; Ahuja, Suchit; Rani, Vibha (Current Cardiology Reviews, 2011)
Regulation of gene expression is central to cell growth, differentiation and diseases. Context specific and signal dependent regulation of gene expression is achieved to a large part by transcription factors. Cardiac transcription factors regulate heart development and are also involved in stress regulation of the adult heart, which may lead to cardiac hypertrophy. Hypertrophy of cardiac myocytes is an outcome of the imbalance between prohypertrophic factors and antihypertrophic factors. This is initially a compensatory mechanism but sustained hypertrophy may lead to heart failure. The growing knowledge of transcriptional control mechanisms is helpful in the development of novel therapies. This review summarizes the role of cardiac transcription factors in cardiac hypertrophy, emphasizing their potential as attractive therapeutic targets to prevent the onset of heart failure and sudden death as they can be converging targets for current therapy.
Keywords: Anthracycline-based chemotherapy